Baray Hokar - Kashfa Samad (Bookgroup, 2024)
"Baray Hokar" by Kashfa Samad is a delightful children's book that captures the imagination of young readers with its engaging storytelling and vibrant illustrations. The story revolves around a young child who learns valuable life lessons through a series of adventures and interactions with various characters.
Keywords: Textbook -- Storybook